2015
DOI: 10.1111/1365-2664.12534
|View full text |Cite
|
Sign up to set email alerts
|

Coho salmon spawner mortality in western US urban watersheds: bioinfiltration prevents lethal storm water impacts

Abstract: Summary Adult coho salmon Oncorhynchus kisutch return each autumn to freshwater spawning habitats throughout western North America. The migration coincides with increasing seasonal rainfall, which in turn increases storm water run‐off, particularly in urban watersheds with extensive impervious land cover. Previous field assessments in urban stream networks have shown that adult coho are dying prematurely at high rates (>50%). Despite significant management concerns for the long‐term conservation of threatened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 33 publications
(67 reference statements)
5
60
1
2
Order By: Relevance
“…; Spromberg et al. ) and was thus strongly correlated with the amount of impervious surface within a watershed (Feist et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Spromberg et al. ) and was thus strongly correlated with the amount of impervious surface within a watershed (Feist et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…, Spromberg et al. ). Adult coho return from the ocean to spawn in basins that span many of the largest metropolitan areas in the Pacific Northwest and Canada (e.g., Portland, Oregon; Seattle, Washington; Vancouver, British Columbia).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies show vegetation not enhancing SBF performance. Spromberg et al (2016) found no difference in the ability of SBF soil with and without vegetation to lower adult Coho mortality when stormwater was filtered through SBF soil and exposed to the adult Coho.…”
Section: Sbfs With and Without Vegetationmentioning
confidence: 75%
“…The U.S. EPA has continued to encourage their use as they help meet NPDES regulatory requirements, are applicable almost everywhere in the U.S., have few limitations (EPA 2012), can be added incrementally (Kloss et al 2006), recharge groundwater (EPA 2016a), and are relatively inexpensive (EPA 2007, Garmestani et al 2012, Houle et al 2013. relative to unexposed controls (Spromberg et al 2016). However, when the same runoff was flowed through SBF media and then into tanks with adult Coho no mortality occurred, highlighting the water quality benefit SBFs provide to receiving water bodies.…”
Section: Bioretention Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation